RELATIONSHIP BETWEEN THE MOTIVATION TO WORK WITH JOB SATISFACTION OF EMPLOYEES IN THE SECRETARIAT OF THE DEPARTMENT OF PUBLIC WORKS EAST DISTRICT KUTAI - Supriadi, Supriadi (PREDIKSI, 2016)
Abstract: Secretariat of Public Works Bureau of East Kutai is the implementation of tasks in thefield of administrative management of administrative, equipment, public administration andgovernance, as well as the implementation of financial administration tasks. Leaders in divided thetask / job is based on a sense of favoritism, only to the employee / certain people and not by themain tasks and functions. This will lead to apathy, not excited, hesitation and fear of being wrong,disappointment, indifference, despair, making the activity that is not running as it should. Thiscauses no job satisfaction.After the authors analysis of the problem, the authors interested in studying the issue of motivationassociated with job satisfaction pegawa. The title of the authors selected in this study are:"Relationship Between Work Motivation by Employee Job Satisfaction In Section Secretariat ofPublic Works Bureau of East Kutai Regency".